Analisis Kesiapan Penerapan Rekam Medis Elektronik dengan Metode Doctor’s Office Quality – Information Technology (Doq – It) di Puskesmas Wiradesa - Brave Satria Fajaryan Utama; Maulina Latifah; Prahita Indriana (STIKES HAKLI Semarang, 2024)
The current development of information technology has made it possible to develop a way of storing and managing data electronically, increasingly better technology and information has had a positive impact on the pattern of development and progress in the field of file storage or file archives. Electronic medical records (EMR) are a solution for managing documents using computer-based or electronic systems in the health sector. This type of research is quantitative descriptive research, namely research carried out to analyze data by describing or illustrating the data that has been collected as it is. The data sources obtained come from primary data in the form of questionnaires and interviews and secondary data from journals, articles, periodicals and so on. In the DOQ – IT method there are 4 aspects of assessment, namely Human Resources, Organizational work culture, leadership governance and IT infrastructure. The research results were assessed from these four aspects. Wiradesa Community Health Center received a score of 93.36 out of 100. This shows that Wiradesa Health Center is ready to implement electronic medical records with a score for each aspect, namely human resources, which received a score of 22.74 out of a maximum score of 25.00. The organization's work culture received a score of 23.44 out of a maximum score of 25.00. Leadership governance received a score of 28.16 out of a maximum score of 30.00. IT Infrastructure scored 19.02 out of a maximum score of 20.00.